Studying the mutual interaction of hydraulic characteristics of waterdistributing pipelines and their spraying devices in the coolers at energy units - Bosak, Nikolai; Cherniuk, Volodymyr; Matlai, Ivan; Bihun, Iryna (Eastern-European Journal of Enterprise Technologies, 2019)
This analytical study is based on the results from hydraulic tests of spray nozzles for the mixing (waterjet) steam condenser at a thermal power plant's turbo generator. The work was performed at the stage of launch operations at TPP. Such hydraulic tests were carried out by co-authors at the stage of launch operations at Razdan TPP (Armenia). The TPP is located in a mountainous region with a limited water supply; the plant's features include: dry cooling of circulating water in the radiator cooling towers; a steam condenser of mixing type. The main tasks of hydraulic tests were: to determine the actual throughput capacity, to find a flow rate coefficient for the nozzles of a steam condenser, as well as analyze their operation in a vacuum in the condenser. This study considered the nozzles that have two openings with a diameter of 13 mm and 15 mm for spraying cooling water within the steam space of the condenser. By exploring the hydraulic characteristics Q=f(H) of standard nozzles mounted at the end of a water-distributing pipeline, it was found that the diameter of the nozzle opening did not significantly affect the flow rate of water under the same water heads. Such a result is explained by that the pipeline's characteristic was obtained, rather than that of the spraying device. The further hydraulic study into the nozzles was performed at a special laboratory bench. The established factor of interrelation between the hydraulic characteristics of a water-distributing pipeline and the nozzles mounted onto it is important for performing similar studies. The throughput capacity of the nozzles, considering the presence of a vacuum in the steam condenser of a turbo generator will be larger than that under atmospheric conditions. However, in a closed system of water circulation, the overall water flow rate of nozzles will equal the supply of cooling water from pumps into a given system. Therefore, the supply of cooling water to a condenser will not change dramatically, while the water flow rate of a single nozzle will be inversely proportional to their number. In addition, we investigated a possibility to increase the feed of water to a condenser in order to improve energy performance. Our analysis reveals the impossibility of a substantial increase in the water supply to a condenser by increasing the diameters of spraying nozzles' openings. This does not substantially reduce the overall loss of water head and feed from circulating pumps to the steam cooling system in a turbine's condenser.